Customized learning materials for a language proficiency course: A look into learners' learning style / Aini Faridah Azizul Hassan, Othman Ismail and Nor Fazlin Mohd Ramli - Azizul Hassan, Aini Faridah; Ismail, Othman; Mohd Ramli, Nor Fazlin (Universiti Teknologi MARA, Kedah, 2015)
Today, there are countless study materials, printed or online, available in the market. Nevertheless, not all the materials are suitable to the learners' need in terms of learning contents, material presentation and especially learning styles. However, with properly customized learning materials, educators will be able to provide their learners with better learning activities and more personalized learning opportunities. In this study, the Felder and Silverman Learning Style Model (FSLSM), is proposed as a probable learning solution for developing the most appropriate and feasible technology-based or self-learning environment. The purpose of using this solution is to cater the different learners' learning styles. A research question was asked on what learning style(s) is/are preferred by the full-time (FT) and distance-learning (ePJJ) learners. An online Index of Learning Styles (ILS) questionnaire was employed as a measuring instrument. A total of 55 learners from two classes, FT and ePJJ at Universiti Teknologi MARA (UiTM) Shah Alam participated in the study during the Sept-Dec 2013 session. The findings reveal that majority are active, sensing, visual and sequential learners. The implication of this study supports the notion that learners' learning styles can affect their success in language learning. Hence, language instructors, who address their learners' learning styles, can provide their learners with a more effective learning environment.